2019
DOI: 10.1002/eco.2141
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeologic setting overrides any influence of wildfire on pore water dissolved organic carbon concentration and quality at a boreal fen

Abstract: Western Boreal Canada could experience drier hydrometeorological conditions under future climatic changes, and the drying of nonpermafrost peatlands can lead to higher frequency and extent of wildfires. Despite increasing pressures, our understanding of the impact of fire on dissolved organic carbon (DOC) concentration and quality across boreal peatlands is not consistent. This study capitalizes on the rare opportunity of having 3 years of prefire and 3 years of postfire DOC data at a treed, moderate‐rich fen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…DOC concentrations in shallow groundwater were similar (except for well B1) in the burned and unburned sections. The result of no change in DOC concentrations after the prescribed burn is similar to other studies that reported no clear effect on DOC concentrations as a result of wildfires [26,27]. While it is unclear what caused the DOC concentration to decrease at well B1, it could have been caused by wetter conditions at this location (Figure 4).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…DOC concentrations in shallow groundwater were similar (except for well B1) in the burned and unburned sections. The result of no change in DOC concentrations after the prescribed burn is similar to other studies that reported no clear effect on DOC concentrations as a result of wildfires [26,27]. While it is unclear what caused the DOC concentration to decrease at well B1, it could have been caused by wetter conditions at this location (Figure 4).…”
Section: Discussionsupporting
confidence: 86%
“…The changes in the optical parameters for wells in the burned section were inconsistent, suggesting that other factors such as hydrology and topography may have influenced the concentration and composition of DOM in shallow groundwater. For example, Davidson et al (2019) found the antecedent hydrological conditions to be the dominant control on DOC concentration along a burn severity gradient in Northern Alberta [26]. found that in a region affected by wildfires, microtopography influenced soil leachate DOM composition based on SUVA and HIX results; samples from hollows exhibited higher aromaticity and degree of humification of DOM [8].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, spatial studies in Sweden and Japan measured significant negative relationships between the percentage of groundwater and DOC concentrations (Egusa et al, 2021;Peralta-Tapia et al, 2015). The importance of groundwater on DOC concentrations after wildfire was also noted following in Alberta, CAN, where there was no measurable impact of wildfire on DOC concentrations in fens (Davidson et al, 2019) or boreal lakes (Olefeldt et al, 2013). Both attributed this lack of wildfire effect to the regulation of DOC concentrations due to the processes of selective adsorption, degradation, and desorption as water and DOC moves slowly downwards through mineral soils to groundwater tables (Kaiser and Kalbitz, 2012).…”
Section: Spatial Stream Network Models Of Docmentioning
confidence: 90%
“…It is likely that multiple compounding factors contributed to the observed result. With many conflicting studies on the influence of water table on DOC dynamics and further debate on the mechanism (Clark et al, 2005(Clark et al, , 2012Davidson et al, 2019;Dieleman et al, 2016;Fenner et al, 2011;Khadka et al, 2015;Strack et al, 2015), this study suggests water table variability should be studied to better understand the relationship between DOC and water table.…”
Section: Hydrological and Physical Controls Of Doc Concentration And ...mentioning
confidence: 97%